2020
DOI: 10.3389/fpubh.2020.585302
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices Among the General Population During COVID-19 Outbreak in Iran: A National Cross-Sectional Online Survey

Abstract: Background: Emerged in December 2019, coronavirus disease 2019 (COVID-19) is one of the largest pandemics ever. During the early phase, little was known about public knowledge, attitudes, and practices (KAP) relating to coronavirus disease. This study was designed to determine KAP of Iranians toward COVID-19.Methods: A cross-sectional online survey was carried out in Iran from February 25 to April 25 using a self-administered questionnaire on 1,480 people. COVID-19-related KAP questions were adapted from other… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 25 publications
2
33
4
Order By: Relevance
“…Among the underprivileged and vulnerable population groups, the dissemination of health education via indigenous languages should be intensified [ 20 ]. Furthermore, in the context of lack of communication and knowledge around recovered patients, awareness campaigns should contribute to the reduction of misconceptions and stigma surrounding these individuals in the community [ 17 ]. Despite poor socioeconomic conditions, the level of knowledge related to COVID-19 and the trust of people in the government and the health system are more likely to influence health-related practices such as self-reporting, self-quarantine, physical distancing, and the use of a face mask.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the underprivileged and vulnerable population groups, the dissemination of health education via indigenous languages should be intensified [ 20 ]. Furthermore, in the context of lack of communication and knowledge around recovered patients, awareness campaigns should contribute to the reduction of misconceptions and stigma surrounding these individuals in the community [ 17 ]. Despite poor socioeconomic conditions, the level of knowledge related to COVID-19 and the trust of people in the government and the health system are more likely to influence health-related practices such as self-reporting, self-quarantine, physical distancing, and the use of a face mask.…”
Section: Discussionmentioning
confidence: 99%
“…The level of KAP varies from country to country. In Iran, people’s knowledge, attitudes, and practices regarding the disease are at a high level despite the existence of misconceptions about the disease [ 17 ]. Evidence from Korea shows that misconceptions surrounding COVID-19 can be avoided through the promotion of public health knowledge and belief in the efficacy of interventions by health officials and policymakers.…”
Section: Introductionmentioning
confidence: 99%
“…34 Similarly, a study in Iran indicated that avoidance of attending overcrowded places and hand washing with soap and water were the predominant preventive behaviors. 48 Moreover, hand washing with soap and water are routinely practiced in religious institutions to prevent the current pandemic. 49 In chronic disease patients, health literacy is one of the main determinant factors for execution of COVID-19 preventive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“… 37 In Iran, 73.2% out of 1,480 respondents stated they would accept an approved COVID-19 vaccine if it were to become available. 38 Many factors influence the vaccine acceptance 35 , 36 , 37 , 38 , 39 including the vaccine efficacy. In Indonesia, a study found that 93.3% out of 1,359 surveyed respondents would like to be vaccinated with the vaccine that has a 95% efficacy but it dropped to 67.0% when the vaccine has 50% efficacy only.…”
Section: Covid-19 Vaccine Challengesmentioning
confidence: 99%